Application of Artificial Neural Network to Predict the Crystallite Size and Lattice Strain of CoCrFeMnNi High Entropy Alloy Prepared by Powder Metallurgy - Cheenepalli Nagarjuna; Sheetal Kumar Dewangan; Ashutosh Sharma; Kwan Lee; 홍순직; 안병민 (Metals and Materials International, 2023)
An equiatomic CoCrFeMnNi high entropy alloy (HEA) was prepared by the gas atomization process. In addition, highenergymilling was carried out to study the effects of milling parameters on the morphology and crystallographic propertiesof HEA powders. Phase identification and morphology of milled powders were observed by X-ray diffraction and scanningelectron microscopy, respectively. Both the atomized and milled powders exhibited a single-phase face-centered cubic solidsolution. The resultant crystallite size (CS) and lattice strain (LS) of milled HEAs were estimated using the WilliamsonHall method and predicted using an artificial neural network (ANN) approach. With increasing the milling time from 0 to240 min, the CS decreased from 39.7 to 6.56 nm and the LS increased from 0.25%–1.48%, respectively. Furthermore, thedeveloped ANN modeling provides an excellent method for the prediction of the CS and LS with excellent accuracies of96.25% and 93.43%, respectively.
Keywords: High-entropy alloys · Powder metallurgy · Artificial neural network · Crystallite size · Lattice strain